2012
DOI: 10.1002/macp.201200402
|View full text |Cite
|
Sign up to set email alerts
|

Novel Chromatic Transitions of Azobenzene‐Functionalized Polydiacetylene Aggregates in 1,2‐Dichlorobenzene Solution

Abstract: Herein, we prepare three azobenzene‐functionalized polydiacetylene (PDA) aggregates in 1,2‐dichlorobenzene solution with reversible thermochromic and novel photo‐induced chromatic behavior. The influence of chemical structural variation on the chromatic transition properties of the PDAs aggregates has been explored in detail by in situ FTIR spectroscopic analyses. The links between chromatic transitions and the molecular structure of PDA aggregates has been established. The results demonstrate that suitable he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The peak corresponding to a mean lateral spacing of 0.40 nm between molecules is probably due to the π–π stacking of the azobenzene moieties . As the temperature increased, the interaction between the azobenzenes in the side chains of DAzo-DA2 weakened and the molecular packing loosened, resulting in distortion of the conjugate orbital array in the PDA and shortening the effective conjugate length. , When the temperature was decreased, the side chain conformation returned to its original molecular structure due to π–π interactions between azobenzene moieties, causing a reversible color change (Figure c). …”
Section: Resultsmentioning
confidence: 98%
“…The peak corresponding to a mean lateral spacing of 0.40 nm between molecules is probably due to the π–π stacking of the azobenzene moieties . As the temperature increased, the interaction between the azobenzenes in the side chains of DAzo-DA2 weakened and the molecular packing loosened, resulting in distortion of the conjugate orbital array in the PDA and shortening the effective conjugate length. , When the temperature was decreased, the side chain conformation returned to its original molecular structure due to π–π interactions between azobenzene moieties, causing a reversible color change (Figure c). …”
Section: Resultsmentioning
confidence: 98%
“…This is in stark contrast to other stimulus-triggered chromism of PDAs, most of which is typically irreversible. Studies have revealed that the reversible thermochromic behaviors of PDAs are largely dependent on the intramolecular noncovalent interactions, i.e., hydrogen bonds, π–π stacking, van der Waals force, etc. ,, In general terms, the stronger the interactions, the better the thermochromic properties of PDAs i.e., reversibility in a wider temperature range. The thermochromic reversibility of PDAs has been achieved by strengthening the intramolecular interactions.…”
Section: Linear Diacetylenes: a Single Polar Headgroup And A Hydropho...mentioning
confidence: 99%
“…Diacetylene monomers per se are photoresponsive once they self-assemble into well-aligned patterns that can go through topochemical polymerization to form PDAs because of the light-sensitive butadiyne moiety. Generally, PDAs can be tailor-made to be light-sensitive by grafting photoresponsive moieties into the headgroups of diacetylenes ,,, or by doping photosensitive moieties that could interact with the headgroups of PDAs into the system . However, Yan et al demonstrated that PDA vesicles without functionalization of the headgroup could also be made light-sensitive via a combination of thin film hydration and supercritical CO 2 fluid treatment .…”
Section: Linear Diacetylenes: a Single Polar Headgroup And A Hydropho...mentioning
confidence: 99%
“…On the other hand, these synthetic procedures are usually laborious and employ expensive chemicals. 18,42 In this context, it can be hypothesized that intermolecular interactions between adjacent monomers can be controlled with other strategies such as the modification of the polymeric matrix and the use of chemical additives. To the best of our knowledge, none of these approaches have been explored in PDA hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…This is because modified monomers (which are structured in parallel in the PDA) can interact with greater or lesser intensity in relation to the original monomers, due to the new chemical groups inserted. On the other hand, these synthetic procedures are usually laborious and employ expensive chemicals. , In this context, it can be hypothesized that intermolecular interactions between adjacent monomers can be controlled with other strategies such as the modification of the polymeric matrix and the use of chemical additives. To the best of our knowledge, none of these approaches have been explored in PDA hydrogels.…”
Section: Introductionmentioning
confidence: 99%